Broadening Perspectives: A Multidisciplinary Collaborative Teaching and Learning Experience - Carol Plummer; Teresa K. Buchanan; C. Barrett Kennedy; Lawrence Rouse; John C. Pine (The University of Alabama, 2022)
Following in the wake of Hurricanes Katrina and Rita and conducted when Hurricanes Gustav and Ike struck the coast of Louisiana, a unique service-learning course stretched the boundaries of students and faculty in new ways. First, students and faculty from five distinctive disciplines designed the course collaboratively, infusing different perspectives into every aspect of planning and teaching. Second, the content area-human impacts of disasters and disease-required students (future leaders who will one day make critical decisions in the midst of uncertainty and conflict) to grapple with major human tragedies. Third, the course objective-to encourage critical analysis-required students to examine multifaceted and complex issues as they considered the environmental, political, and social effects of disaster and disease. Finally, this course used a qualitative research project as its service component, and the partner was our own university. The goal of the project was to offer information that would help the administration plan for future disasters. Students directly experienced disaster-related challenges through planned assignments requiring critical analysis and a ropes challenge experience simulating a crisis environment. In the first few weeks of class, proving that in education as in life timing is everything, Hurricane Gustav severely damaged the community and simulation became reality. While this course, entitled Honors 2000: Critical Analysis and Social Responsibility: The Human Response to Disaster and Disease, is not precisely replicable because of unique hurricane occurrences, any team of faculty can replicate the collaboration, flexibility, responsiveness, and authenticity that characterized the experience.